The influence of bridge geometry and welding chamber height on microstructure and mechanical properties for porthole die extrusion of AA6082 - Yu Wang; Andrew Zang; Mary Wells; Warren J Poole; Nick Parson (Journal of Materials Research and Technology)
This study investigates the effects of bridge geometry and welding chamber height on the microstructure and mechanical properties of AA6082 aluminum extrusions using electron backscatter diffraction (EBSD), tensile testing, and numerical simulations. EBSD results showed that a shallow welding chamber with a flat bridge geometry produced CubeRd (∼40 %), Cube (∼15 %) and Goss (∼15 %) texture components along the welding seam, whereas the corresponding texture was mainly Copper (50–80 %) for material extruded using the other three geometries, i.e., shallow streamlined, deep streamlined and deep flat. Tensile tests using digital image correlation (DIC) revealed strain localization at the weld seam for all geometries, with the shallow flat die exhibiting the most severe peak strain (∼0.22 at a far-field strain of 0.12) compared to ∼0.16 for streamlined bridges. Increasing the welding chamber height for the streamlined bridge had almost no effect on the mechanical properties of the extruded sample. However, in the flat bridge case, the same increase significantly altered both the texture and mechanical properties. DEFORM® (Design Environment for FORMing) 3D simulations of the thermal-mechanical history showed that the shallow flat die extrusion experienced a higher exit temperature and effective plastic strain compared to the other die designs which allow for the rationalization of the texture differences between the different dies.